Kebebasan dalam Filsafat Eksistensialisme Jean Paul Sartre - Firdaus M. Yunus (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
Existentialism puts humans at the center point of all human relationships. It is rooted in an effort to keep a distance with all hegemony to discover the existence and the essence of self. Human must be conscious of his humane to find out the existence of himself (l'Ãªtre-en-soi). Since, it is believed that no other creatures besides humans that exists. Freedom is the essence of human beings; usually humans are always free to create him-self. Humans are free to organize, select and can give meaning to reality.